ANALYSIS OF FINANCIAL ACCOUNTING STANDARD STATEMENT 71 ON PROVISIONING FOR RECEIVABLE LOSSES - Mustafa, Nurhikmah; S, Masnawaty; Azis, Fajriani (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This study aims to analyze Financial Accounting Standard Statement 71 on the provision of receivable losses at PT Pelindo Jasa Maritim Subholding. Data collection techniques are carried out by conducting interviews and documentation. The data analysis technique is carried out by descriptive analysis by describing the findings based on the results of the data collected. The results of this study are that PT Pelindo Jasa Maritim has suppressed the movement of the impairment loss reserve in 2020 by 20.86%, while allowance for impairment losses for 2021 is 9.72% so it can be concluded that the determination, recognition and measurement of the impairment loss reserve at PT Pelindo Jasa Maritim, has been in accordance with Financial Accounting Standard Statement 71 from 2020-2021 even though seen from the percentage of credit still fluctuates. Financial Accounting Standard Statement 71 is very helpful in financial reporting and a significant allowance for impairment losses is included in the calculation of credit losses, the determination of this reserve depends on how much the four estimated future cash flows are to determine individual reserves.